Empowering internationalisation: FBM forges global academic alliances - UiTM, Faculty of Business and Management (UiTM, 2024)
This initiative is expected to bring significant benefits not only to academic staff and researchers but also to students, who will gain international exposure and broader leaming experiences. FBM believes that such cross-border collaborations will serve as a catalyst for innovation, academic excellence, and the development of globally competitive human capital.